2023
DOI: 10.3390/plants12193384
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathic Activity of a Novel Compound, Two Known Sesquiterpenes, and a C13 Nor-Isopenoid from the Leave of Croton oblongifolius Roxb. for Weed Control

Seinn Moh Moh,
Shunya Tojo,
Toshiaki Teruya
et al.

Abstract: Investigation of allelopathic substances from herbal plants may lead to the development of allelochemical-based natural herbicides. Croton oblongifolius (Roxb.) is a well-known herbal plant with a long history of being used for traditional medicines and for being the source of a diverse range of bioactive compounds. This plant has been reported to have allelopathic potential; however, its allelopathic-related substances have not yet been described. Therefore, we conducted this investigation to explore the alle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 49 publications
(57 reference statements)
2
5
0
Order By: Relevance
“…Additionally, the different I 50 values of the A. marmelos extracts for the hypocotyl/coleoptile and root growth of L. sativum , L. sativa , M. sativa , E. crusgalli , L. multiflorum , and P. pretense indicate that the inhibitory effect of the extracts depends on the six examined plant species ( Table 1 ). Similar results of dose- and species-dependent allelopathic properties have been documented by other researchers [ 36 , 37 , 38 ]. The growth inhibitory activity of the A. marmelos extracts against the six plant species investigated in this study indicates that these extracts may involve active compounds that have growth-suppressive properties.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, the different I 50 values of the A. marmelos extracts for the hypocotyl/coleoptile and root growth of L. sativum , L. sativa , M. sativa , E. crusgalli , L. multiflorum , and P. pretense indicate that the inhibitory effect of the extracts depends on the six examined plant species ( Table 1 ). Similar results of dose- and species-dependent allelopathic properties have been documented by other researchers [ 36 , 37 , 38 ]. The growth inhibitory activity of the A. marmelos extracts against the six plant species investigated in this study indicates that these extracts may involve active compounds that have growth-suppressive properties.…”
Section: Discussionsupporting
confidence: 91%
“…These growth-inhibitory effects are in agreement with the findings from our earlier investigation. In our earlier study, we found that C. oblongifolius extracts inhibited the growth of four plants (two dicots, L. sativum and L. sativa, and two monocots, E. crusgalli and P. pratense) [39]. Additionally, the IC50 values of the extracts used against the hypocotyls/coleoptiles and roots of M. sativa and L. multiflorum (in this present research)…”
Section: Discussionsupporting
confidence: 67%
“…Based on the IC 50 results, the root growth of the two plant species in the current study and the four plant species in the prior study [39] showed greater susceptibility to the C. oblongifolius leaf extracts than the hypocotyl/coleoptile growth. Roots are more susceptible to plant extracts than hypocotyls or coleoptiles, because they come into direct contact with the allelochemicals during germination [49,50].…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations